Uji Pemangsaan dan Tanggap Fungsional Predator Chysoperla carnea Stephens (Neuroptera: Crysopidae) Terhadap Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) - I WAYAN DIRGAYANA; I WAYAN SUPARTHA; I NYOMAN WIJAYA (Agrotrop : Journal on Agriculture Science, 2021)
Predation and Functional Response Test of Predator Chysoperla carnea Stephens (Neuroptera: Crysopidae) Against Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae). This study aims to evaluate the predatory capacity of C. carnea by measuring the rate of searching capacity and handling-time of one prey and its functional response to the population density of P. manihoti. The research was conducted at the Integrated Pest Management Laboratory (IPMLab), Faculty of Agriculture, Udayana University. The study was conducted from February to May 2019. Testing of functional responses used a randomized block design with 5 treatments (3, 6, 9, 12, 15 nymphs-3) each of which was repeated 10 times. The results showed that the prey searching-capacity when the population was low (3 nymphs-3) took longer (10.37 minutes), while when the population was high it took a short time (6.23 minutes). The length of time for handling one prey in the low population was 6.08 minutes, while in the high population it was 5.48 minutes. Predator C. carnea has a tpe-2 functional response to an increase in the population of P. manihoti nymphs with the equation Y = 4.32x / 1 + 1.973x (R2 = 0.980). The rate of predation increases sharply when the population of low increases, and decreases when the increase of prey population increases. C. carnea has the potential to be developed as a control agent for P. manihoti.